Dynamics of abscission of reproductive structures in common bean access - Orsi, Nicole; Moraes, Caroline; Lara-Fioreze, Ana Carolina da Costa; Fioreze, Samuel Luiz (Revista de Ciências Agroveterinárias, 2021)
Genotypes from the Andean and Mesoamerican gene pool can present contrasting behavior for reproductive structures fixation. The subject of this study was to determine the dynamics associated with the abscission of reproductive structures for common bean accesses from Andean and Mesoamerican gene pools in protected cultivation conditions. The experiment was carried out in a greenhouse, using seven common bean accesses from Embrapa Arroz e Feijão and the experimental design consisted of a randomized complete block design. The evaluations made were based on the number of days to begin flowering, flowering period, number of emitted flowers per plant, number of flower buds, flowers and pods aborted per plant, total number of pods per plant and number of seeds per plant.Certain characteristics were considered to be highly significant, such as the amount of days to begin flowering, the flowering period, percentage of aborted pods and number of harvested pods. The Mesoamerican accesses that presented greater abortion also produced more flowers, which suggests that abortion of reproductive structures can be a natural adjustment of the plant. Andean accessions with shorter reproductive period showed greater pod abortion. The dynamics of flower and pod abscission in the common bean proved to be widely variable depending on the different gene pools and genotypes evaluated and due to growth habit.